Fertilizer use in semiarid West Africa: Profitability and supporting policy - Shapiro, Barry I.; Sanders, J.H. (Elsevier, 1998)
In semiarid West Africa, inorganic fertilizer use and sustainability objectives are complementary. With increasing population pressure and low levels of purchased inputs, crop yields in many regions are declining. Moderate use of inorganic fertilizer is required for increasing yields in a sustainable way. Where infiltration is a problem, a water-retention technique reduces the risk and increases the returns from fertilization. In the sandy dune soils, fertilization and higher densities are sufficient to raise farm incomes at acceptable risk levels.